2010
DOI: 10.1021/jm100395q
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 3-[2-(Imidazo[1,2-b]pyridazin-3-yl)ethynyl]-4-methyl-N-{4-[(4-methylpiperazin-1-yl)methyl]-3-(trifluoromethyl)phenyl}benzamide (AP24534), a Potent, Orally Active Pan-Inhibitor of Breakpoint Cluster Region-Abelson (BCR-ABL) Kinase Including the T315I Gatekeeper Mutant

Abstract: In the treatment of chronic myeloid leukemia (CML) with BCR-ABL kinase inhibitors, the T315I gatekeeper mutant has emerged as resistant to all currently approved agents. This report describes the structure-guided design of a novel series of potent pan-inhibitors of BCR-ABL, including the T315I mutation. A key structural feature is the carbon-carbon triple bond linker which skirts the increased bulk of Ile315 side chain. Extensive SAR studies led to the discovery of development candidate 20g (AP24534), which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
228
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 333 publications
(240 citation statements)
references
References 49 publications
3
228
0
9
Order By: Relevance
“…We recently reported the design and preclinical evaluation of ponatinib (Table 1), a potent inhibitor of native BCR-ABL, BCR-ABL T315I , and other resistant mutants (IC 50 : 0.5-36 nM) (53)(54)(55). Ponatinib inhibited all tested BCR-ABL mutants in cellular and biochemical assays, suppressed BCR-ABL T315I -driven tumor growth in mice, and completely abrogated resistance in cell-based mutagenesis screens, confirming its profile as a pan-BCR-ABL inhibitor.…”
Section: Targeting the Bcr-abl T315i Mutant: Clinical Candidatesmentioning
confidence: 99%
“…We recently reported the design and preclinical evaluation of ponatinib (Table 1), a potent inhibitor of native BCR-ABL, BCR-ABL T315I , and other resistant mutants (IC 50 : 0.5-36 nM) (53)(54)(55). Ponatinib inhibited all tested BCR-ABL mutants in cellular and biochemical assays, suppressed BCR-ABL T315I -driven tumor growth in mice, and completely abrogated resistance in cell-based mutagenesis screens, confirming its profile as a pan-BCR-ABL inhibitor.…”
Section: Targeting the Bcr-abl T315i Mutant: Clinical Candidatesmentioning
confidence: 99%
“…Finally, dovitinib (TKI258) inhibits the kinase activity of FGFR1, FGFR2, and FGFR3 and the cellular activity of FGFR3 in models of multiple myeloma (34,35). Ponatinib (AP24534) is an oral multitargeted kinase inhibitor that potently inhibits native and mutant forms of BCR-ABL (36)(37)(38) and is currently being investigated in a phase II pivotal trial in patients with chronic myelogenous leukemia (CML; Clinicaltrials.gov: NCT01207440). Initial characterization of the kinase selectivity profile of ponatinib showed that it exhibits potent in vitro biochemical activity, with IC 50 values <20 nmol/L, against 40 additional kinases including all 4 FGFRs (37).…”
Section: Introductionmentioning
confidence: 99%
“…The following two cases illustrate how it can steer property‐based lead optimization to improve pharmacokinetics. The first example is the optimization of third‐generation BCR‐ABL kinase inhibitors, starting from the lead BCR‐ABL‐1 with poor pharmacokinetics, distant from the egg, to finally obtain the oral anticancer drug ponatinib 20. Ponatinib correctly lies inside the white ellipse, but inside the BOILED‐Egg′s yolk, too (blue path in Figures 2 b and S9).…”
mentioning
confidence: 99%